Cosmetic use-related adverse events: findings from lay public in Malaysia - Ab. Hadi, Hazrina; Ai, Nur'ain; Zamli, Mazlina; Awadh, Ammar Ihsan Jawad; Zafar, Muhammad Zeeshan; Jamshed, Shazia Qasim (Multidisciplinary Digital Publishing Institute (MDPI) AG, 2020)
Objectives: Although the occurrence of adverse cosmetic reactions is often underestimated by the consumers, the documentation of the incident might be helpful for the authority in regulating the cosmetic products. The objectives of this study were to assess the prevalence and type of adverse cosmetic event (ACE), as well as the measures adopted by those experiencing the ACE. Methods: A cross-sectional descriptive study was conducted using a structured questionnaire comprised of 11 questions. The questionnaire was divided into two sections: demographic profile and adverse cosmetic reaction. A total of 552 cosmetic users in Malaysia participated in this study. Data were entered into Statistical Package for Social Sciences (SPSS) version 20 and descriptive statistics was applied. Findings: A total of 29% respondents have experienced ACEs. Eczema was found to be the most frequent type of ACE. Facial area (n = 178) was reported to be the most frequent body site affected by ACEs. A mere 41% attempted to consult health professionals. Conclusions: Few respondents consulted health professionals for recommendations, indicating that they misjudge occurrences related to adverse outcomes. The high diversity and non-specificity of cosmetic adverse reactions reported in the current research highlighted the need for a vigorous cosmetovigilance system.